Conception and validation of the Quality of Educators' Observation and Planning Practices Scale (QEOPPS). Issue 2 (27th May 2021) - Lemay, Lise; Cantin, Gilles; Lemire, Julie; Bouchard, Caroline
Abstract: The objective of this paper is to present the conception and validation of the Quality of Educators' Observation and Planning Practices Scale (QEOPPS). The instrument assesses the quality of early childhood educators' observation practices (observing children, collecting information, using the collected information, paying attention to each child) and planning practices (planning regularly, tailoring planning to each child, implementing it with flexibility, planning based on a curriculum). This study was conducted with 181 educators working in early childhood education and care centres with 3- to 5-year-olds. Based on educators' responses in a semi-structured interview and on verification of relevant documents, an observer scored the QEOPPS. The results indicate that the QEOPPS shows good inter-rater reliability and internal consistency, and also provide evidence for construct and concurrent validity. The discussion highlights the implication of the QEOPPS as a promising scale for use in research and as support for initial and ongoing training for practice.